CLINICAL-STATISTICAL STUDY ON THE FREQUENCY OF WISDOM TOOTH INCLUSION PATHOLOGY - Dorin Ioan Cocoș; Eugen Bud; Mariana Păcurar; Carmen Galea; Calin Alina; Kamel Earar (Romanian Journal of Oral Rehabilitation)
Including wisdom teeth is a common problem in dental practice, associated with significant complications such as gum inflammation, caries, root resorption of neighboring teeth, and cyst formation. This clinical-statistical study analyzed the frequency and distribution of wisdom tooth inclusion pathology according to age and anatomical location, within a group of 50 patients aged between 19 and 65 years, divided into five age categories. The data obtained through clinical examinations and imaging were analyzed using specialized software to correlate the clinical results with those from the plaster models made for diagnostic purposes. The results of the study show a higher frequency of wisdom tooth inclusion in the mandibular compared to the maxilla, partial inclusion being more common in the lower quadrants. Also, the incidence is highest in the 19-25 age group. Treatment options range from periodic monitoring to extraction, depending on the associated symptoms and complications. The conclusions of the study emphasize the importance of early diagnosis and careful monitoring to prevent complications and optimize the management of this common pathology.